SKOPE—Study of Ketorolac vs Opioid for Pain after Endoscopy: A Double-Blinded Randomized Control Trial in Patients Undergoing Ureteroscopy. Issue 2 (5th August 2021) - Fedrigon, Donald; Faris, Anna; Kachroo, Naveen; Jain, Rajat; Elia, Marlie; Wilkins, Lamont; Li, Jianbo; De, Smita; Noble, Mark; Monga, Manoj; Sivalingam, Sri
Abstract : Purpose: Pain is the leading cause of unplanned emergency department visits and readmissions after ureteroscopy, making postoperative analgesic stewardship a priority given the current opioid epidemic. We conducted a double-blinded, randomized controlled trial, with noninferiority design, comparing nonsteroidal anti-inflammatory drugs to opiates for postoperative pain control in patients undergoing ureteroscopy for urolithiasis. Materials and Methods: Patients were randomized and blinded to either oxycodone (5 mg) or ketorolac (10 mg), taken as needed, with 3 nonblinded oxycodone rescue pills for breakthrough pain. Primary study outcome was visual analogue scale pain score on postoperative days 1–5. Secondary outcomes included medication utilization, side effects, and Ureteral Stent Symptom Questionnaire scores. Results: A total of 81 patients were included (43 oxycodone, 38 ketorolac). The 2 groups had comparable patient, stone, and perioperative characteristics. No differences were found in postoperative pain scores, study medication or rescue pill usage, or side effects. Higher maximum pain scores on days 1–5 (p <0.05) and higher questionnaire score (28.1 vs 21.7, p=0.045) correlated with analgesic usage, irrespective of treatment group. Patients receiving ketorolac reported significantly fewer days confined to bed (mean±SD 1.3±1.3 vs 2.3±2.6, p=0.02). There was no difference in unscheduled postoperative physician encounters. Conclusions: This is the first double-blinded randomized controlled trial comparing nonsteroidal anti-inflammatory drugs and opiates post-ureteroscopy, and demonstrates noninferiority of nonsteroidal anti-inflammatory drugs in pain control with similar efficacy, safety profile, physician contact and notably, earlier convalescence compared to the opioid group. This provides strong evidence against routine opioid use post-ureteroscopy, justifying continued investigation into reducing postoperative opiate prescriptions.